Engagement in moderate-intensity physical activity supports overnight memory retention in older adults - Miranda G. Chappel-Farley; Destiny E. Berisha; Abhishek Dave; Rachel M. Sanders; Christopher E. Kline; John T. Janecek; Negin Sattari; Kitty K. Lui; Ivy Y. Chen; Ariel B. Neikrug; Ruth M. Benca; Michael A. Yassa; et al. (Scientific Reports)
Abstract Preserving the ability to vividly recall emotionally rich experiences contributes to quality of life in older adulthood. While prior works suggest that moderate-intensity physical activity (MPA) may bolster memory, it is unclear whether this extends to emotionally salient memories consolidated during sleep. In the current study, older adults (mean age = 72.3 ± 5.8) completed an overnight polysomnography assessment with emotional memory tested before and after sleep and a self-report questionnaire assessing habitual PA. Results show that better negative emotional memory consolidation was associated with the frequency and duration of MPA. Statistically replacing 30 min of lower-intensity activity with MPA was associated with better negative emotional memory consolidation. MPA may enhance sleep-dependent consolidation of negative memories in older adults, with modest increases in MPA yielding significant consolidation benefits. Findings may guide interventions and inform public health recommendations by demonstrating that substituting even short durations of low-intensity activity for MPA could produce significant cognitive gains in older adulthood.